2017
DOI: 10.4034/pboci.2017.171.11
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Distance Between the Mental Foramina using ConeBeam Computed Tomography: A Pilot Study with a Possible Method for Planning Mandibular Implants

Abstract: Objective: To identify the average number of dental implants that can be placed in the lower anterior region to support a fixed mandibular prosthesis based on the distance between the mental foramina, using a cone beam computed tomography (CBCT) scan through a new method of measurement. Material and Methods: Eighty-two CT scans from a total sample of 1,465 exams were selected. The method to measure the space between the foramina was developed using the BlueSky Plan3 software in Dicom format and the axial recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…36 However, there have been a pause in such study until the revisits by several authors in the millennium. 5,13,15,37,38 13 The current finding is closer to the measurement reported by Guo et al (2009) and is in agreement with the measurement reported by Vane Swetah & Jayanth Kumar (2019). 15,37 Difference in measurements in the studies performed after the millennium against those reported in the 1930s may be related to the technique used, or difference in the population whereby the current samples may have benefitted from better living condition and nutrition.…”
Section: Authorssupporting
confidence: 93%
See 4 more Smart Citations
“…36 However, there have been a pause in such study until the revisits by several authors in the millennium. 5,13,15,37,38 13 The current finding is closer to the measurement reported by Guo et al (2009) and is in agreement with the measurement reported by Vane Swetah & Jayanth Kumar (2019). 15,37 Difference in measurements in the studies performed after the millennium against those reported in the 1930s may be related to the technique used, or difference in the population whereby the current samples may have benefitted from better living condition and nutrition.…”
Section: Authorssupporting
confidence: 93%
“…They found that a universal treatment plan cannot be followed in their Indian subjects due to the short interforamina distance of 38.9 mm in their subjects. In agreement with them, Marieiro et al (2017) reported most of their subjects could be rehabilitated using a protocol with 4 implants of 3.3mm diameters. In contrast, the finding of current study suggests that Malaysian Mongoloids had sufficient space to receive the so-called OD-5 prosthesis, i.e., five implants rigidly joined with a bar.…”
Section: Authorssupporting
confidence: 75%
See 3 more Smart Citations